2016
DOI: 10.1016/j.neuroimage.2015.07.079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on value-directed modulation of semantic network activity during verbal learning

Abstract: While impairments in memory recall are apparent in aging, older adults show a remarkably preserved ability to selectively remember information deemed valuable. Here, we use fMRI to compare brain activation in healthy older and younger adults during encoding of high and low value words to determine whether there are differences in how older adults achieve value-directed memory selectivity. We find that memory selectivity in older adults is associated with value-related changes in activation during word presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
95
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(108 citation statements)
references
References 86 publications
11
95
2
Order By: Relevance
“…Recent work concerning value-based learning and selectivity indicates that the study of high-value information relative to low-value information, in anticipation of a recall test, is associated with greater activity in regions of semantic processing (Cohen, Rissman, Suthana, Castel, & Knowlton, 2014, 2016). If RgRc participants’ recognition in Experiment 2 was based more on recollection than familiarity judgments, this could have made the transition to a purely recall-based test format less jarring, in that participants could have adapted encoding strategies already being used in anticipation of recognition testing for the recall tests.…”
Section: Methodsmentioning
confidence: 99%
“…Recent work concerning value-based learning and selectivity indicates that the study of high-value information relative to low-value information, in anticipation of a recall test, is associated with greater activity in regions of semantic processing (Cohen, Rissman, Suthana, Castel, & Knowlton, 2014, 2016). If RgRc participants’ recognition in Experiment 2 was based more on recollection than familiarity judgments, this could have made the transition to a purely recall-based test format less jarring, in that participants could have adapted encoding strategies already being used in anticipation of recognition testing for the recall tests.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described (Ariel & Castel, 2013;Cohen, Rissman, Suthana, Castel, & Knowlton, 2016), the SI is a measure of a participant's point score, after taking into account the ideal point score and the chance point scores, which is weighted by the number of words recalled. The ideal point score is the maximum number of points that can be earned for recalling n number of words (e.g., the ideal point score for recalling four words is 10 + 10 + 10 + 10 = 40).…”
Section: Si ¼mentioning
confidence: 99%
“…While the present research is focused only on healthy young adults, our recent work on older adults provides a particularly illustrative example of this point. Cohen, Rissman, Suthana, Castel, and Knowlton (2014, 2016) used fMRI to examine the neural mechanisms underlying value-related memory enhancement in a paradigm known as value-directed remembering (Castel, Benjamin, Craik, & Watkins, 2002; Castel, 2008). These studies found that in both young adults and older adults, the degree to which value affects brain activity during word encoding in brain regions related to strategic control of semantic processing correlates with individual differences in how strongly value affects memory on an immediate free recall test.…”
mentioning
confidence: 99%
“…Such findings suggest that the impact of value on memory outcomes might qualitatively differ based on interactions between the mechanism being invoked and the time scale on which memory is being tested. Finally, as discussed above, effects of value on dopamine-producing regions during encoding may be weakened in older adults, even as strategy-driven value effects on memory are maintained with healthy aging (Cohen et al, 2016). It is thus important that we gain a better understanding of the interplay between strategy-driven and non-strategic, dopamine-driven effects of value in order to fully understand how value affects memory encoding processes.…”
mentioning
confidence: 99%